Erectile dysfunction therapy after prostate cancer treatment. Issue 2 (15th February 2022) - Stainer, Victoria; Skews, Rachel; Aning, Jonathan J
Abstract : Erectile dysfunction (ED) is a common complication of prostate cancer treatment. In the second of this two‐part series on the management of erectile dysfunction following treatment for localised prostate cancer, the authors discuss the therapeutic options available for ED after prostate cancer treatment and their advantages and disadvantages.